Trust as a Catalyst for Community Development - Kuzmuk, Olga M. (Instytut Spraw Administracji Publicznej, Lublin, Poland, 2024)
The article analyzes the role of trust as a catalyst for community development, which is particularly relevant in the context of modern socio-political challenges. Trust serves as the foundation of social cohesion, ensuring active citizen engagement in decision-making processes, the implementation of local initiatives, and the formation of shared responsibility. The importance of this topic increases in light of social instability and global crises, which demand effective and coordinated responses from society. The author investigates the mechanisms of trust formation and explores the underlying factors of social cohesion among community members. Special attention is given to how openness, transparency, and collaboration can enhance trust at all levels. The conclusions emphasize the importance of trust in the context of sustainable development and the progress of local communities. It is established that trust not only contributes to effective governance but is also a critical element in the formation of resilient and prosperous communities in the modern world. Thus, understanding the role of trust as a catalyst for community development can serve as a basis for developing new approaches to addressing socio-political issues at the local level.
Keywords: trust; Community development; Social cohesion; Civic engagement; Local initiatives; Social stability